2023
DOI: 10.1029/2022wr032828
|View full text |Cite
|
Sign up to set email alerts
|

Seawater–Groundwater Interaction Governs Trace Metal Zonation in a Coastal Sandy Aquifer

Zhenyan Wang,
Qianqian Wang,
Yifan Guo
et al.

Abstract: Trace metals in the groundwater of coastal sandy aquifers significantly influence the coastal ecosystem, yet the spatiotemporal controls of these metals remain unclear. In this paper, we comprehensively revealed the distribution patterns, key controlling factors, potential ecological risks, and fluxes to the ocean of groundwater trace metals (As, Ba, Cr, Cd, Fe, Mn, Pb, and Zn) in a coastal deep sandy aquifer. The results showed a clear zonation of trace metals in the groundwater in relation to the mixing exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…However, numerous studies observed that elevated concentrations of heavy metals, even in minor quantities, precede the natural accumulation of heavy metals in plant tissues, affecting their metabolism and functional means [55]. Elevated concentration of Pb can cause abrupt brain development [56], Cd could cause acute and chronic diseases [57], and Cu is used in the treatment of anemia, bone weakness, and cardiovascular issues [47] at elevated concentrations.…”
Section: Heavy Metal Dynamics In Seawater-induced Aquatic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous studies observed that elevated concentrations of heavy metals, even in minor quantities, precede the natural accumulation of heavy metals in plant tissues, affecting their metabolism and functional means [55]. Elevated concentration of Pb can cause abrupt brain development [56], Cd could cause acute and chronic diseases [57], and Cu is used in the treatment of anemia, bone weakness, and cardiovascular issues [47] at elevated concentrations.…”
Section: Heavy Metal Dynamics In Seawater-induced Aquatic Systemmentioning
confidence: 99%
“…An interplay between evaporation, tides, waves, and precipitation could potentially cause highly intricate driving mechanisms, which significantly influence the subsurface flow patterns and transport of solutes or contaminants [37,46]. Numerous studies have concluded that seawater intrusion has major control over the concentration of contaminants in aquifers [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…In coastal regions, interactions of seawater and freshwater bring about unique groundwater environment, numerous endeavors have investigated chemical releasing and accumulations, biological environmental problems, and different coastal carbon budgets (e.g. Luo et al, 2022;Xiao et al, 2022;Zhang et al, 2022;Wang et al, 2023). Furthermore, in coastal karst aquifers, the seawater-freshwater interactions may be amplified since the existence of interconnected conduit systems (Arthur et al, 2007;Fleury et al, 2007).…”
Section: Introductionmentioning
confidence: 99%